Digital Literacy And Ai Adoption In Midwifery Education: Enhancing Career Readiness For The Society 5.0 Healthcare Landscape - Masniah Masniah; Rusdinor Rusdinor; Nor Ikhsan; Khuzaini Khuzaini; Syahrial Shaddiq (PT. AHLAL PUBLISHER NUSANTARA, 2026)
The Society 5.0 era demands that midwifery students possess career readiness integrated with digital technology. However, the effectiveness of digital literacy and Artificial Intelligence (AI) adoption in determining the career readiness of prospective midwives still requires in-depth study. This research aims to analyze the influence of digital literacy and AI adoption on the career readiness of students at the Darussalam Martapura Midwifery Academy. This quantitative study employed an explanatory design with a Total Sampling technique involving 66 respondents. Data were collected through digital questionnaires and analyzed using multiple linear regression and t-tests. The results indicate that digital literacy has a positive and significant effect on career readiness (t count 41.459; p-value < 0.05). Conversely, AI adoption partially has no significant effect on career readiness (t count1.572; p-value > 0.05). Simultaneously, both variables contribute 96.5% to career readiness (R2 = 0.965). Digital literacy is the primary predictor of student career readiness, while AI adoption is still perceived as a secondary tool. Educational institutions need to integrate AI into the clinical curriculum so that students can perceive the relevance of such technology in the future midwifery profession.